2017
DOI: 10.18632/aging.101168
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic clock analysis of diet, exercise, education, and lifestyle factors

Abstract: Behavioral and lifestyle factors have been shown to relate to a number of health-related outcomes, yet there is a need for studies that examine their relationship to molecular aging rates. Toward this end, we use recent epigenetic biomarkers of age that have previously been shown to predict all-cause mortality, chronic conditions and age-related functional decline. We analyze cross-sectional data from 4,173 postmenopausal female participants from the Women's Health Initiative, as well as 402 male and female pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
558
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 567 publications
(656 citation statements)
references
References 93 publications
57
558
14
Order By: Relevance
“…These correlations could suggest that reductions in the integrity of the immune and inflammation systems drive accelerated aging in DNAm (or vice versa), or the convergence of these metrics of cellular aging could be due to a distinct and more basic biological process. Related to this, Chen et al [55], Quach et al [79], and Horvath et al [80] combined data from DNAm age and white blood cell counts to create a new index of immune system aging in blood. They showed that this new metric out-performed other age-adjusted DNAm age estimates in predicting important outcomes, such as time until death [55], and a variety of cardiometabolic measures [79].…”
Section: Potential Mechanisms Linking Traumatic Stress To Acceleratedmentioning
confidence: 99%
See 2 more Smart Citations
“…These correlations could suggest that reductions in the integrity of the immune and inflammation systems drive accelerated aging in DNAm (or vice versa), or the convergence of these metrics of cellular aging could be due to a distinct and more basic biological process. Related to this, Chen et al [55], Quach et al [79], and Horvath et al [80] combined data from DNAm age and white blood cell counts to create a new index of immune system aging in blood. They showed that this new metric out-performed other age-adjusted DNAm age estimates in predicting important outcomes, such as time until death [55], and a variety of cardiometabolic measures [79].…”
Section: Potential Mechanisms Linking Traumatic Stress To Acceleratedmentioning
confidence: 99%
“…Related to this, Chen et al [55], Quach et al [79], and Horvath et al [80] combined data from DNAm age and white blood cell counts to create a new index of immune system aging in blood. They showed that this new metric out-performed other age-adjusted DNAm age estimates in predicting important outcomes, such as time until death [55], and a variety of cardiometabolic measures [79]. Though chronological age was regressed out of this combined metric of DNAm age and immune system age, one concern about this approach was that the immune system components used to form this index were selected on, and weighted by, their univariate associations with chronological age (in a separate dataset).…”
Section: Potential Mechanisms Linking Traumatic Stress To Acceleratedmentioning
confidence: 99%
See 1 more Smart Citation
“…Some types of cancer are associated with increased epigenetic aging rates (e.g. Moreover, although the clock may reflect the potential consequences of intrinsic and programmed cellular events during the aging process, it is affected by other external factors such as viral infections, including HIV [59], obesity [60], and metabolic syndromes [61]. basal breast cancer) [19,56].…”
Section: Current and Future Challenges To Understanding Epigenetic Vamentioning
confidence: 99%
“…Regardless, recently researchers have begun to question whether the methylation signal determined by cell mix should be discarded as a merely a technical artefact. Horvath et al [19] and Quach et al [49] found their intrinsic and extrinsic signals of aging in blood correlated with different lifestyle factors and outcomes. Cell mix driven DNA methylation signal may be extremely relevant to prognostic biomarkers and trackers of intervention efficacy.…”
Section: Is Cell MIX a Confounder To Be Discarded?mentioning
confidence: 99%